THE EUROPEAN UNION AND THE ‘NEW WAR’ FROM ITS EASTERN BORDERS - Miruna TRONCOTĂ (EURINT, 2016)
There is enough evidence to claim that since 2014 a new type of war is waged in Ukraine, which is novel in terms of methods, strategies, tactics, and level of human sacrifice. It is an ongoing discussion between experts, scholars and policy makers whether the Ukrainian crisis showed the limits of the European Union’s (EU) approach to conflict resolution, or, on the contrary, it served as a chance to redesign its approach towards its neighbourhoods and refine its instruments in order to more efficiently contain conflicts under the leadership of Federica Mogherini. The aim of the article is to identify the characteristics of the 'New War' paradigm in the context of recent political developments after the annexation of Crimea and the ongoing open conflict in Eastern Ukraine. The purpose of this paper is to reveal both the conceptual clarity of this theoretical paradigm, against its critics, but also to emphasise its policy importance for strengthening EU conflict resolution strategies. The article also points to the fact that after the wide process of reviewing the European Security Strategy conducted between 2015 and 2016, the EEAS finally launched a new approach in dealing with EU troubled neighbourhoods, which contains numerous elements borrowed from the ‘new war’ paradigm and the concept of human security.